Different Shades of Beauty: Adolescents’ Perspectives on Drawing From Observation - Wolk, Nurit; Barak, Adi; Yaniv, Dani (Frontiers in Psychology, 2020)
ABSTRACT Background: Drawing from observation (DFO) is an art therapy method that entails drawing an object, along with guided reflections on process and outcome. In this qualitative study, we explored adolescents’ perspectives on their DFO experience, and how they perceive it as having influenced their emotional well-being. Methods: We interviewed 10 adolescents who participated in a DFO group, regarding their perspectives on DFO. Participants were asked to refer to their experience as well as to provide examples of their drawings. Through a thematic analysis we integrated data from interviews and drawings. Results: Adolescents experienced three lines of tension in DFO: Between self-acceptance and self-judgment, between merging and separation, and between similarities and differences. Processing these tensions has the potential to increase their emotional well-being. Conclusions: DFO could make a meaningful contribution to adolescents’ emotional well-being. The unique intersection between object, observation, and drawing in art-therapy addresses adolescents’ emotional-developmental challenges.